Rhetoric Balaghah in Arabic Literary Works During the Abbasid Period - Irmasani Daulay (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The Abbasid period (750–1258 CE) represents one of the most significant phases in the development of Arabic literary and intellectual traditions. During this period, Arabic literature flourished through the extensive use of rhetorical and balaghah techniques, enriching both its aesthetic and philosophical dimensions. This study aims to analyze how rhetorical and balaghah elements were applied in Arabic literary works of the Abbasid era and to examine their role in conveying social, moral, and intellectual meanings. The research employs a qualitative approach through textual analysis of selected works by prominent Abbasid authors, including al-Jahiz, al-Mutanabbi, and al-Buhturi. The analysis focuses on identifying rhetorical devices such as tasybih (simile), isti‘arah (metaphor), majaz (figurative expression), and rhetorical argumentation within the selected texts. The findings reveal that rhetorical and balaghah techniques function not only as stylistic devices for beautifying language but also as important tools for constructing persuasive discourse, expressing philosophical reflections, and articulating social and cultural values within Abbasid society. In particular, the poetry of al-Mutanabbi demonstrates a strong use of metaphorical and rhetorical structures to emphasize themes of honor and power. At the same time, al-Jahiz's prose works illustrate how rhetorical argument can convey intellectual ideas about knowledge and wisdom. These findings confirm that rhetorical creativity played a central role in shaping the intellectual and aesthetic character of Abbasid literature. The study contributes to classical Arabic literary scholarship by providing a contextual interpretation of rhetorical practices and highlighting the relationship between language, literature, and intellectual culture in the Abbasid period.